2014
DOI: 10.1007/s40596-014-0085-z
|View full text |Cite
|
Sign up to set email alerts
|

Involuntary Detention: Comparison of Clinical Practices of Psychiatry Residents and Faculty

Abstract: Inconsistency of documented clinical justification for involuntarily detention was higher among residents compared to faculty. There is a need for structured training and supervision of psychiatry residents as well as updated training for faculty psychiatrists with regard to involuntary detention procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…32,33 , which may cause misuse or abuse of the criteria by psychiatrists 34,35 . Furthermore, research has identified different interpretations of IA criteria among psychiatrists even though there are clear regulations in the local legislation 34,36,37 , which means that psychiatrists may be more inclined to make decisions according to their professional judgement but not the legal provisions 34,36 . Third, psychiatrists play central roles in balancing the interests of the public with protecting the legal rights of mental disorder patients 3842 , especially regarding circumstances in which patients do not present significant signs or clear risk of harming themselves or others 34,40 .…”
Section: Discussionmentioning
confidence: 99%
“…32,33 , which may cause misuse or abuse of the criteria by psychiatrists 34,35 . Furthermore, research has identified different interpretations of IA criteria among psychiatrists even though there are clear regulations in the local legislation 34,36,37 , which means that psychiatrists may be more inclined to make decisions according to their professional judgement but not the legal provisions 34,36 . Third, psychiatrists play central roles in balancing the interests of the public with protecting the legal rights of mental disorder patients 3842 , especially regarding circumstances in which patients do not present significant signs or clear risk of harming themselves or others 34,40 .…”
Section: Discussionmentioning
confidence: 99%
“…They included 31 empirical articles 2 , 7 18 , 20 , 22 26 , 28 – 37 , 40 , 42 44 , 46 56 , 59 , 42 – 44 , 46 , 48 , 51 , 55 , 56 , 59 and 21 descriptive, review, or commentary articles. 1 , 6 , 16 , 17 , 19 , 21 , 27 , 30 , 32 , 38 , 39 , 41 , 45 , 47 , 49 , 50 , 52 – 57 , 58 , 58 Geographical spread included the Republic of Ireland, 9 , 28 , 47 , 48 , 59 UK, 1 , 2 , 6 10 , 15 20 38 44 49 , 50 57 , 38 – 44 , 46 , 49 , 50 , 52 , 54 – 57 Canada, 27 , ...…”
Section: Resultsmentioning
confidence: 99%
“…1 , 6 , 16 , 17 , 19 , 21 , 27 , 30 , 32 , 38 , 39 , 41 , 45 , 47 , 49 , 50 , 52 – 57 , 58 , 58 Geographical spread included the Republic of Ireland, 9 , 28 , 47 , 48 , 59 UK, 1 , 2 , 6 10 , 15 20 38 44 49 , 50 57 , 38 – 44 , 46 , 49 , 50 , 52 , 54 – 57 Canada, 27 , 32 US, 21 , 25 , 29 37 , 45 , 51 , 58 , 58 Australia, 26 and South Africa. 53 The range of professional groups involved included GPs, 9 , 10 , 28 , 36 , 42 , 59 medical students, 27 psychiatrists, 23 , 29 , 34 , …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation